Perbaikan Hasil Belajar Laporan Keuangan pada Mata Pelajaran Ekonomi melalui Metode Inkuiri - Nuraidah, Sitepu (JUPIIS: Jurnal Pendidikan Ilmu-ilmu Sosial, 2015)
This research aims to boosts learning outcome by using method of inquiry on the subject of Economy at grade XI in SMA 12 of Medan in 2013/2014 school year. The teaching method used was method of inquiry. Whereas the tools of collecting data used were obser-vation and essay test at the and of interfering class had done. The research consists of two cycle, which both the first and second cycle consists of the problems and steps of planning, implementing, observating, data analysing and reflecting. The result of research shows that using method of inquiry on subject of Economy can be elevate learning outcome of students at grade XI in SMA 12 of Medan in the 2013/2014 school year. It can be viewed by average of the first test score of 42.1 with passing level of 10.5 percent. Yet after treating class of first cycle, average score of studentsâ learning achievement increased on 61.6 with completing learning level on 31.6 percent. While in the second cycle studentsâ average score climbed to 78.9 with completing learning level on 86.8 percent. Then it can be infered that using method of inquiry on subject of Economy could be elevate learning incomes of students at class XI in SMA 12 of Medan.